White noise insole: an artificial evoked sensation device that can be expected to improve plantar sensation of diabetic foot - Yangzheng Jiang (Scientific Reports, 2023)
Abstract Diabetic foot is a common severe complication of diabetes, and its main symptom is diabetic foot ulcer. The production of plantar diabetic foot ulcers is usually affected by two factors, namely neuropathy or vascular disease. While previous studies proved that stochastic resonance (SR) could effectively enhance the plantar touch of patients with diabetic feet, the potential impact of SR on neural circuit feedback, especially on the input of the tactile nerves of the lower limbs, is less clear. This study aims to explore the potential impact on the tactile threshold of the human foot when using vibrating insoles. We study a white noise vibration insole based on SR mechanism. We compare and analyze the tactile threshold voltage (TTV) triggered by an electrical stimulation device in three main plantar pressure-bearing areas (the second metatarsal (M2), the fourth metatarsal (M4), and the heel (H) area) of 8 participants using EEG and self-developed vibration insole. Significance found in M2 and M4 areas, white noise signal (WNS) lowered the tactile threshold in these areas, and had a potentially positive impact on patients with diabetic feet, especially in the M4 area. The influence of WNS on the plantar heel area was still controversial. This study showed that WNS applied to the sole could improve the plantar tactile sensing ability of patients with diabetic feet, but it did not cover all areas. The application of WNS showed better benefits for the forefoot area than for the hindfoot area, which was speculated that may be related to the difference in the distribution density of blood vessels in plantar areas. Due to the impaired natural touch in participants with diabetic foot, using artificial evoked sensation WNS intervention, would be a feasible approach to improve plantar sensation.